PENGARUH KONSEP DIRI, MOTIVASI BERPRESTASI, DAN PERSEPSI PROFESI GURU TERHADAP MINAT MENJADI GURU EKONOMI - Sindi Mallyanti; I Komang Winatha; Yon Rizal (FKIP Unila, 2020)
This research aims to determine the influence of self-concept, achievement motivation, and the perception of the teacher profession towards the interest of being a economic teacher in Economics education Student in 2018 and 2019. The method used in this research is a descriptive verification with the ex post facto approach and survey in which the population of this study amounted to 126 respondents and the sample obtained amounted to 95 respondents. Data collection using questionnaire. Hypothesis testing partially T-test and simultaneous F-test. Based on the results of the analysis obtained the conclusion that there is an individual influence between self- concept, achievement motivation, and the perception of the teacher's profession towards the interest of being a economic teacher in economics education students FKIP Lampung University class 2018 and 2019. While simultaneously there is also a influence between self-concept, achievement motivation, and the perception of the teacher profession towards the interest of being a economic teacher in economics education students FKIP Lampung University class of 2018 and 2019 Fcalculate value of 9.904 with Sig. of 0.000. Penelitian ini bertujuan untuk mengetahui pengaruh konsep diri, motivasi berprestasi, dan persepsi profesi guru terhadap minat menjadi guru ekonomi pada mahasiswa Pendidikan Ekonomi Angkatan 2018 dan 2019. Metode dalam penelitian ini menggunakandeskriptif verifikatif dengan pendekatan ex post facto and survey yang dimana populasi penelitian ini berjumlah 126 responden dan sampel yang diperoleh berjumlah 95 responden. Pengumpulan data menggunakan angket/kuisioner. Pengujian hipotesis secara parsial Uji t dan secara simultan Uji F. Berdasarkan pada hasil analisis diperoleh kesimpulan bahwa terdapat pengaruh secara individu antara konsep diri, motivasi berprestasi, dan persepsi profesi guru terhadap minat menjadi guru pada mahasiswa Pendidikan Ekonomi FKIP Universitas Lampung angkatan 2018. Sedangkan secara simultan juga terdapat pengaruh antara konsep diri, motivasi berprestasi, dan persepsi profesi guru terhadap minat menjadi guru pada mahasiswa Pendidikan Ekonomi FKIP Universitas Lampung angkatan 2018 dan 2019. Nilai Fhitung sebesar 9,904 dengan sig. sebesar 0,000. Kata kunci: konsep diri, minat menjadi guru, motivasi berprestasi, persepsi profesi guru